Inclusive Education in Practice: Challenges and Strategies for Mainstreaming Special Needs Students - Dr. Najma Begum; Imran Badshah (Journal of Religion and Society, 2025)
Inclusive education has become a global priority or goal supported by the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) and the Sustainable Development Goal 4 (Quality Education). However, even with policy frameworks that endorse equitable access, mainstreaming of special needs students into normal school settings is not doing well; especially in low- and middle-income nations. The current research is an investigation of the modern state of inclusive practice in mainstream public schools in terms of pedagogical approaches, institutional preparedness, and the experience of teachers, administrators, and parents. Based on the Social Model of Disability, the Sociocultural Theory developed by Vygotsky, and the Universal Design of Learning (UDL), the study would use a qualitative design that comprises semi-structured interviews, focus group, classroom observation, and reviews of documents. These results demonstrate the existence of sharp differences regarding the teacher preparedness, infrastructural facilities, and community involvement. Inclusive strategies have been shown in only a select number of schools, with differentiated instruction, peer scaffolding, and active family engagement representing only some of the most prominent ones, with many schools facing systemic limitations such as underfunding, lack of training opportunities, and cultural stigma. The figures also show an apparent implementation gap between policy requirements and practice at the ground level. According to thematic analysis, only multi-stakeholder cooperation, the policy tailored to the context, and institutional responsibility makes sustainable inclusion a reality. This paper ends with action-related recommendations to close the policy-practice gap by specifically recommending teacher training, investment in infrastructure, community, and curriculum change. Finally, the study highlights the need to redefine inclusive education as a kind of intervention but as a central feature of equitable and quality education of all students. Keywords: Inclusive Education, Mainstreaming, Special Needs Students, Universal Design For Learning, Teacher Training, Educational Equity, Disability Inclusion, Qualitative Research, Public Schools, Educational Policy.